2001
DOI: 10.1128/aac.45.3.794-799.2001
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Response to Repeated Moxifloxacin or Levofloxacin Exposure in a Rabbit Tissue Cage Model

Abstract: The role of moxifloxacin and levofloxacin pharmacokinetics (PK) in antimicrobial efficacy and in the selection of fluoroquinolone-resistant Streptococcus pneumoniae strains was investigated using the rabbit tissue cage abscess model. A rabbit tissue cage was created by insertion of sterile Wiffle balls in the dorsal cervical area. Animals orally received a range of moxifloxacin or levofloxacin doses that simulate human PK for 7 days 48 h after the Wiffle balls were inoculated with fluoroquinolone-sensitive S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…Similar observations for levofloxacin were made previously with in vitro and animal pharmacokinetic models using different techniques (13,14 , and we observed a similar phenomenon with moxifloxacin in this in vitro model. It was previously suggested that the emergence of resistance is more likely in strains with efflux pumps than in those without efflux pumps, and some data from in vitro pharmacokinetic models support this notion (Madaras-Kelly et al, 40th ICAAC).…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations for levofloxacin were made previously with in vitro and animal pharmacokinetic models using different techniques (13,14 , and we observed a similar phenomenon with moxifloxacin in this in vitro model. It was previously suggested that the emergence of resistance is more likely in strains with efflux pumps than in those without efflux pumps, and some data from in vitro pharmacokinetic models support this notion (Madaras-Kelly et al, 40th ICAAC).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, detection of the emergence of resistance by comparison of pre-and postexposure MICs may not be as sensitive for detecting changes in resistance as PAPs. Animal data obtained in a rabbit tissue cage model with S. pneumoniae and moxifloxacin exposure for 7 days failed to show any emergence of resistance (17). The exception to these observations in both in vitro and animal models appears to be ciprofloxacin; data indicating resistance detected by changes in MICs or PAPs are easily generated by ciprofloxacin exposure (4,16,18).…”
Section: Discussionmentioning
confidence: 84%
“…Urine concentrations were measured at these collection times by a validated high-performance liquid chromatographic method [6]. The mean (±S.D.)…”
Section: Urine Samplesmentioning
confidence: 99%